Pematangan Psikologis Orang Tua Mempengaruhi Penurunan Angka Anak Yang Terdampak Stunting (Jurnal Pustaka, 2025)
In Indonesia, stunting in children is still a serious problem. In terms of preventing stunting in children, parents play a very important role in efforts to prevent stunting in their children. Parents can provide the support and care their children need, by maintaining their physical and psychological health. The purpose of this paper is to determine the psychological maturation of parents which can influence the reduction in the number of children affected by stunting. The writing method for this article uses the literature review method. The findings obtained show that psychological maturation of parents can influence the reduction in the number of children affected by stunting. When parents feel uncertain about their child's growth, they may lack confidence in taking the necessary actions to prevent stunting.
Keywords: Stunting; Psychological Maturation; Parents